1998
DOI: 10.1523/jneurosci.18-23-10037.1998
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Differential Activation of Mitogen-Activated Protein Kinase Cascades by Unfamiliar Taste in the Insular Cortex of the Behaving Rat

Abstract: Rats were given to drink an unfamiliar taste solution under conditions that result in long-term memory of that taste. The insular cortex, which contains the taste cortex, was then removed and assayed for activation of mitogen-activated protein kinase (MAPK) cascades by using antibodies to the activated forms of various MAPKs. Extracellular responsive kinase 1-2 (ERK1-2) in the cortical homogenate was significantly activated within Ͻ30 min of drinking the taste solution, without alteration in the total level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
209
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(232 citation statements)
references
References 59 publications
(80 reference statements)
20
209
2
1
Order By: Relevance
“…Similar results have been obtained in the lateral nucleus of the amygdala in the consolidation of fear memory (Schafe et al, 2000), where Zif268 is also activated (Hall et al, 2000;Malkani and Rosen, 2000). Moreover, coordinated activation of MAPK/ ERK, CREB and Elk-1 has also been reported in the hippocampus after one-trial avoidance learning (Cammarota et al, 2000) and in the insular cortex in association with long-term storage of taste memory (Berman et al, 1998). Together, these data suggest, but do not prove, that the same transduction mechanisms via the MAPK/ERK cascade that are implicated in LTP, are recruited in different structures and pathways to mediate learning-induced Zif268 expression.…”
Section: Role Of Mapk In Zif268 Transcriptionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been obtained in the lateral nucleus of the amygdala in the consolidation of fear memory (Schafe et al, 2000), where Zif268 is also activated (Hall et al, 2000;Malkani and Rosen, 2000). Moreover, coordinated activation of MAPK/ ERK, CREB and Elk-1 has also been reported in the hippocampus after one-trial avoidance learning (Cammarota et al, 2000) and in the insular cortex in association with long-term storage of taste memory (Berman et al, 1998). Together, these data suggest, but do not prove, that the same transduction mechanisms via the MAPK/ERK cascade that are implicated in LTP, are recruited in different structures and pathways to mediate learning-induced Zif268 expression.…”
Section: Role Of Mapk In Zif268 Transcriptionsupporting
confidence: 80%
“…A crucial event in signal transduction leading to gene regulation in neurons is the activation of protein kinases. Although several kinases, including protein kinase C (PKC), protein kinase A (PKA), ␣-calmodulin protein kinase II (␣CaMKII), and the tyrosine kinases, are known to play an important role in LTP (for review, see Soderling and Derkach, 2000), recent work suggests that the MAPK/ERK cascade, a complex kinase cascade implicated in cell differentiation and proliferation, is essential for long-term synaptic plasticity Sweatt, 1996, 1997) and for certain types of learning (Berman et al, 1998;Atkins et al, 1998;Blum et al, 1999), and is a likely candidate for mediating the transcriptional response associated with synaptic plasticity. In cell lines, experimental evidence suggests that MAPK/ERK, once activated, translocates to the nucleus where it can regulate transcriptional activity of many IEGs (reviewed in Treisman, 1996).…”
Section: Role Of Mapk In Zif268 Transcriptionmentioning
confidence: 99%
“…For example, our laboratory has shown that intrahippocampal PD098059 administration blocks longterm memory in the water maze task without any effect on short-term memory (Blum et al 1999). In addition, it has been reported that PD098059 administration blocks longterm memory in taste aversion, fear conditioning, and passive avoidance tasks (Berman et al 1998;Schafe et al 1999;Walz et al 1999). In this report, we have used PD098059 to investigate the role of Erk activity in the EC in long-term spatial memory.…”
mentioning
confidence: 89%
“…This test session is defined as extinction training since animals are exposed to nonreinforced presentations of a conditioned stimulus (CS; eg, saccahrine) that had previously been paired with a fear-inducing unconditioned stimulus (US; eg, LiCl). Under these conditions, the conditioned rats preferred water to saccharin at a ratio of 9:1 in a multiple choice test situation (Berman et al, 1998). Multiple-bottle tests are more sensitive than one-bottle tests to obtain an aversion index.…”
Section: Behavioral Proceduresmentioning
confidence: 99%